Statistical optimisation of xylanase production by estuarine Streptomyces sp. and its application in clarification of fruit juice - Emilda Rosmine; Neethu Changanedassery Sainjan; Reshma Silvester; Aneesa Alikkunju; Saramma Aikkarakunnath Varghese (Journal of Genetic Engineering and Biotechnology, 2017)
Recently, xylanase has become an essential option for environmental friendly industrial biotechnological applications and the rising demand for its large scale production urge to take the advantage of statistical approach of optimization to investigate the interactive effects of prominent process factors involved to enhance xylanase production. In the present study, xylanase production from Streptomyces sp. strain ER1 isolated from Cochin estuarine soil; was optimised using statistical designs- Plackett-Burman and Central composite design. Plackett-Burman design was used to identify important fermentation condition factors affecting the xylanase production using beechwood xylan as the substrate. The optimum levels of these significant factors were determined employing the Central Composite Design. Out of the thirteen factors screened, concentration of beechwood xylan and olive oil, agitation speed, and inoculum age were recognized as the most significant factors. By analyzing the response surface plots and using numerical optimization method, the optimal levels for concentration of xylan and olive oil, agitation speed and inoculum age were determined as 0.37%, 33.10 mg/L, 42.87 RPM and 21.05 h, respectively. The optimised medium resulted in a 1.56-fold increased level of the xylanase (10,220 U/mL) production compared to the initial level (3986.444 U/mL) after 120 h of fermentation. The purified enzyme could successfully clarify orange, mousambi and pineapple juice to 20.87%, 23.64% and 27.89% respectively. Thus the present study has proved that Streptomyces sp. strain ER1 (KY449279) is a potential and useful organism for xylanase production and its purified enzyme could clarify the selected fruit juices.